Hajj and its spiritual education in the development of akhlaq: Ideal and challenges - Abd Rashid, Adnan (Leen and Luna International, Chikusei, Japan, 2018)
The performance of Hajj, which constitutes the fifth of The Pillars of Islam, is obligatory cibadah for those who can afford to perform it once during their lifetime. It includes particular types of devotional acts such as Ihram, tawaf, sa’e, wuquf, jamrah and so on which a Muslim can offer in Makkah alone. It essentially needs physical exertion and the bearing of hardship, the sacrificing of wealth, energy, time and love and requires great patience in order to perform its devotions properly. Muslims from all parts of the world leave their lands, home, family and travel to Makkah simply for the cause of Allah to serve Him Alone, to whom belongs all Praise, all Grace and all Sovereignty. In fact, the performance of Hajj was originally to follow the shari’at and imitate the example of the Prophet Ibrahim, who believed totally in the Oneness of Allah and rejected all other deities, who totally surrendered and submitted his whole life for the cause of Allah and sacrificed absolutely to the Will of Allah. The Muslims who perform their Hajj with a sincere intention of the pleasure of Allah will return to their fitrah of goodness in which Allah created them. However, present situation in Makkah the real destruction of the ideal Hajj is the pilgrims themselves who have lost their discipline, patience and tolerance during the performance of the acts of Hajj. We do not deny that the acts of Hajj require physical exertion, but the atmosphere of pushing and shoving and sometimes shouting and disputing among those performing the Hajj in order to carry out the acts, such as tawaf, kissing the Black Stone and so on, indicate that perhaps the verses of the Qur’an are not penetrating their hearts. Actually, these bad deeds, such as pushing others and disputing, are sins which are unconsciously committed by some of the pilgrims and may discredit the performance of Hajj before Allah. This concept paper attempt to discuss the ideal of hajj and the challenges in performing hajj for the pleasure of Allah which will return to fitrah of goodness.